Spontaneous Splenic Rupture in Plasmodium Vivax Malaria - Sufyan, Abu; Zaman, Muhammad; ., Manzoor; ., Qadir; ., Saifullah (Pakistan Armed Forces Medical Journal, 2022)
Splenomegaly is one of the common complications of malaria most commonly associated with Plasmodium Vivax. Due to inadequate treatment, spleen can harbor parasite, which causes recurrent infection leading to splenomegaly and splenic rupture. Spleen is more prone to rupture in acute phase of infection. The exact mechanism of splenic rupture is still unknown but trauma, pressure of abdominal muscles on spleen due to sneezing and coughing plays important rule. Spontaneous splenic rupture although very rare in normal sized spleen, as in case presented here, is life-threatening complication. Therefore, early diagnosis and management plays important role in saving life.